Effect of Defoliation on Harvested Yield of Buffel Grass - Butt, Nasir M; Donart, Garry B; Southward, Morris G; Pieper, Rex D; Mohammad, Noor (Annals of Arid Zone, 2016)
The simulated grazing study on buffel grass (Cenchrus ciliaris L) was carried out during summer growing seasons of 1986 and] 987 at the forage and pasture research block of National Agricultural Research Centre, Islamabad, Pakistan. Four cutting height and four cutting interval treatments were applied in all possible combinations. Individual plant yield and the yield per hectare showed similar response to clipping treatments. Harvested yield of buffel grass was influenced by the combined action of harvesting interval and cutting height indicating the importance of both factors in the management of buffel grass pastures. Maximum harvested yields were obtained by clipping the grass at very low clipping height (10 cm stubble height) after very short interval of cutting (3-week interval). This indicated resistance of this grass to frequent as well as intensive clipping.